2011
DOI: 10.5194/acpd-11-11311-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observation and modelling of OH and HO<sub>2</sub> concentrations in the Pearl River Delta 2006: a missing OH source in a VOC rich atmosphere

Abstract: Ambient OH and HO2 concentrations were measured by laser induced fluorescence (LIF) during the PRIDE-PRD2006 (Program of Regional Integrated Experiments of Air Quality over the Pearl River Delta, 2006) campaign at a rural site downwind of the megacity of Guangzhou in Southern China. The observed OH concentrations reached daily peak values of (15–26) × 106 cm−3 which are among the highest values so far reported for urban and suburban areas. The observed OH shows a consist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(118 citation statements)
references
References 95 publications
11
105
2
Order By: Relevance
“…The impact of interferences from RO 2 is highest, if the oxidation rate of pollutants such as alkenes including isoprene is high (high VOC and OH concentrations) but NO concentrations are small as found e.g. during the PRIDE-PRD2006 campaign (Lu et al, 2011). For this campaign, model calculations suggest that the measured HO 2 concentrations contain an interference by RO 2 of at least 30 % during daytime.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The impact of interferences from RO 2 is highest, if the oxidation rate of pollutants such as alkenes including isoprene is high (high VOC and OH concentrations) but NO concentrations are small as found e.g. during the PRIDE-PRD2006 campaign (Lu et al, 2011). For this campaign, model calculations suggest that the measured HO 2 concentrations contain an interference by RO 2 of at least 30 % during daytime.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a significant impact of the interference is expected for the recently published HO x measurements performed during the PRIDE-PRD2006 campaign in the Pearl River Delta, China . Model calculations suggest that the measured HO 2 concentrations contain an interference by RO 2 of at least 30 % during daytime, depending on the chemical mechanism used for the calculation of the RO 2 species (Lu et al, 2011). This also suggests that the unknown radical recycling, proposed by Hofzumahaus et al (2009) to explain the observed OH, must be even larger, if the HO 2 concentrations are smaller than assumed before (Lu et al, 2011).…”
Section: Implication For Atmospheric Ho 2 Concentration Measurements mentioning
confidence: 98%
See 1 more Smart Citation
“…Observations of atmospheric OH concentrations indicate that under low NO x conditions isoprene may be involved in a so far unidentified recycling mechanism that converts HO 2 into OH 1022 A. Kiendler-Scharr et al: Effects on new particle formation and OH concentrations without involving ozone formation (Tan et al, 2001;Thornton et al, 2002;Ren et al, 2008;Lelieveld et al, 2008;Hofzumahaus et al, 2009;Whalley et al, 2011;Lu et al, 2011). Contrary, suppression of new particle formation by isoprene was ascribed to its suppression of OH concentrations (Kiendler-Scharr et al, 2009b).…”
Section: Introductionmentioning
confidence: 94%
“…Air was continuously sampled from the chamber by gas expansion through a 0.6 mm nozzle into a low pressure (6 hPa) detection cell, in which OH was detected by pulsed laser-excited fluorescence at 308 nm. Unlike in previous instrument configurations (Holland et al, 2003;Lu et al, 2011), a long inlet tube (anodized aluminium) with a length of 22 cm and an internal diameter of 3.9 cm connected the nozzle to the fluorescence cell. This allowed in-situ measurement of OH in the reaction chamber at a distance of about 20 cm from the chamber bottom and the sidewall surfaces.…”
Section: Instrumentationmentioning
confidence: 99%